The Use of Factorial Planning in the Investigation of Structural Electronics Property for the Rational Design of Benzophenone Derivatives - Passamani, Fabiana; Guerra, Isadora Auróra; Filgueiras, Paulo Roberto; Santos, Bianca Aloise Maneira Corrêa; Gonçalves, Arlan da Silva (Orbital: The Electronic Journal of Chemistry, 2022)
Human exposure to ultraviolet (UV) radiation leads photochemical excitation processes in the skin, causing problems to human health. The use of photoprotectors helps to minimize these intrinsic hazards. Benzophenone molecules stand out for the absorption of energy in the UVA and UVB range and structural changes in these, it is an area of ​​interest to obtain safer and more effective molecules. This work applied the full factorial design methodology 24 in an investigation by molecular modeling using semi-empirical method PM7, in order to evaluate the impact generated on the decrease of the energy GAP with the insertion of OH (level +) and H (level –-). The results showed unfavorable and favorable contributions between interactions and in the main effect, and the compounds disubstituted in ortho and para position for the same aromatic ring showed a better percentage of contribution, indicating that these conditions are relevant for greater reactivity compared to the others. Thus, we conclude that the use of the experimental planning methodology is an ally in obtaining information for planning new protective filtersmore stable and safe.